Eating habits matter for sleep difficulties in children and adolescents: A cross-sectional study - Yaping Zhao; Diyang Qu; Kaixin Liang; Ran Bao; Ran Bao; Sitong Chen (Frontiers in Pediatrics, 2023)
BackgroundSleep difficulties are a common sleep-related problem among children and adolescents. However, the association between eating habits and sleep difficulties has not been extensively studied. Therefore, this study aimed to investigate the relationship between eating habits and sleep difficulties in children and adolescents.MethodsThis study utilized cross-sectional data from the 2013/2014 Health Behaviour in School-aged Children survey. A total of 213,879 young adolescents provided self-reported information on their weekday and weekend breakfast consumption, fruit and vegetable intake, sweet and soft drink consumption, and sleep difficulties. Covariates such as sex, age, family affluence, physical activity, and body mass index were also assessed. Multilevel generalized linear modelling was used to analyse the association between independent and dependent. Results were reported as odds ratios (OR) with 95% confidence intervals.ResultsOf all study participants, approximately 50% were girls. Regression models indicated that more frequent breakfast consumption was associated with fewer sleep difficulties (e.g., consuming breakfast on weekdays for 5 days: OR = 1.49, 95% CI: 1.45–1.54). Fruit and vegetable consumption once a week or more was also linked to fewer sleep difficulties (all OR > 1.08, ≥ 1.07). In addition, consuming fewer sweets and soft drinks was generally associated with fewer sleep difficulties.ConclusionThis study provides evidence supporting the association between healthier eating habits and reduced sleep difficulties in children and adolescents. Future research using longitudinal or experimental designs is encouraged to confirm or negate these findings. Additionally, this study offers practical guidance for nutritional counselling professionals and sleep health promotion practitioners.